Internalisasi Nilai-Nilai Budi Pekerti dalam Hikayat Nakhoda Asyik - Supriadi, Dedi (Manuskripta, 2022)
This article discusses the problems of internalizing moral values ​​in the Malay literary work entitled Hikayat Nakhoda Asyik. As an old literary work, the text written in the Jawi script using the Betawi Malay language and became a guide for the development of character in the past, became the uniqueness and novelty of this literary work. The aim of this research is to portray the internalization of cultural values ​​and moral values in Hikayat Nakhoda Asyik. This study employed a perspective-based philological discourse analysis approach to obtaining a complete description of the texts written in Jawi script using Betawi Malay. The findings show that Hikayat Nakhoda Asyik contains moral values ​which are categorized into three parts, namely characters towards God who is the creator of the universe; second, manners to human beings; and third, manners to the environment. Hence, the duty of human being as a khalīfah fī al-ard (leader on earth) becomes harmonious and mercy to the universe. === Artikel ini membahas masalah internalisasi nilai-nilai budi pekerti dalam karya sastra melayu Hikayat Nakhoda Asyik. Sebagai karya sastra lama, teks manuskrip ini yang ditulis dengan aksara jawi dengan pemakaian bahasa Melayu Betawi ini menjadi pedoman pengembangan budi pekerti di masa lampau, ini kemudian yang menjadi keunikan tersendiri terhadap karya sastra ini. Adapun tujuan penelitian ini yaitu, mendeskripsikan internalisasi nilai budaya dalam Hikayat Nakhoda Asyik dan mendeskripsikan internalisasi nilai-nilai budi pekerti dalam teks. Penelitian ini menggunakan pendekatan analisis teks menggunakan perspektif filologi untuk mendapatkan gambaran secara utuh terhadap isi teks yang ditulis dengan aksara jawi dengan pemakaian bahasa Melayu Betawi. Hasil analisis menunjukkan bahwasanya Hikayat Nakhoda Asyik mengandung nilai-nilai budi pekerti yang dikelompokkan menjadi tiga bagian yaitu budi pekerti kepada Tuhan yang maha pencipta sekalian alam; kedua, budi pekerti kepada sesama manusia; dan ketiga, budi pekerti kepada alam sekitar. Dengan demikian trias panca kehidupan manusia sebagai khalīfah fī al-ard (pemipin di muka bumi) menjadi harmonis dan menjadi rahmat bagi semesta.